Ta’zīz Mahārah al- Kalām bistikhdām Ṣuwar Kārikātūriah al-Awwal fī Qismi Taʿlīm al-Lughah al-‘Arabiyyah Jāmi’ah al-Islamiyah Nahḍah al-‘Ulama Kotabumi Lampung Shamāl - Rahayu, Puji; Zamroni, Muh (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to strengthen students' speaking skills. The low quality of speaking learning for Arabic Language Education (PBA) students for the 2023/2024 academic year shows that many students complain when they are appointed to speak in class. They feel confused about determining the material or topic of discussion or are not yet able to speak in class using Arabic. because lecturers have not implemented speaking learning using media so that students are able to develop ideas for finding conversation material and dare to speak Arabic in class. This type of research is Classroom Action Research (PTK), on STAINU Kotabumi Lampung second semester Arabic Language Education students with a total of 33 students, data collection techniques in the form of observation, questionnaires, tests and interviews. The use of caricature drawing media can improve speaking learning outcomes for students in the second semester of Arabic Language Education at STAINU Kotabumi Lampung. The results of student learning achievement in cycle I were 57.5% or as many as 19 students. In cycle II the learning completion results were 90.9% or as many as 30 students. Students feel interested when they are involved and active in the process learning. and students are enthusiastic about participating in learning because they use caricature drawing media to strengthen their speaking skills. Active student involvement will create the learning process becomes more meaningful.